Soft foods for easier eating cookbook : easy-to-follow recipes for people who have chewing and swallowing problems - Woodruff, Sandra L. (Square One Publishers, 2010)
You prepared as best as you could for the procedure. You followed your doctor's advice to the letter, and to your relief, the treatment went well. But you didn't expect the pain and difficulty you are now experiencing as you try to chew and swallow. The simple act of eating is no longer simple; it has become pure torture. Each year, medical treatments leave millions of patients unable to eat normally. Most hospitals deal with this problem simply by puréeing whatever food they are cooking. Needless to say, the result is not very appetizing, so many people refuse to eat, making it impossible to obtain adequate nutrition, maintain a healthy weight, and help the body heal. To help ease them through this difficult--and many times, unexpected--period, nutritionists Sandra Woodruff and Leah Gilbert-Henderson have written the Soft Foods for Easier Eating Cookbook. Here is an easy- to-follow guide designed to provide maximum nutrition and taste with minimum discomfort.